Advances in the pharmacotherapy of Heart Failure: type 2 sodium-glucose cotransporter Inhibitors (SGLT2) as a therapeutic option (Research, Society and Development, 2023)
Despite the therapeutic options currently available for Heart Failure (HF), this pathology is still responsible for high rates of morbidity and mortality in the population. Faced with these current therapeutic limitations, the development of studies to evaluate the effectiveness of new drugs in HF is justified, among them the sodium-glucose cotransporter type 2 (SGLT2) inhibitors. In this context, the objective of this work is to evaluate the benefits and limitations of SGLT2 inhibitors in the management of HF. The present study is an integrative literature review carried out from the PubMed and VHL databases. Seven randomized clinical studies controlled by placebo were analyzed, from which it was verified that SGLT2 inhibitors presented promising therapeutic effect, with cardioprotective and renoprotective action, in a broad spectrum of HF, reducing the risk of hospitalizations and deaths from causes cardiovascular effects, regardless of the presence or absence of DM2, in addition to being safe and well tolerated. Therefore, the use of SGLT2 inhibitors represents an additional effective and safe therapeutic alternative with the potential to modify the morbidity and mortality of HF.